Female genital mutilation: Knowledge, attitude and practices of Flemish midwives. Issue 3 (March 2015) - Cappon, Sien; L'Ecluse, Charlotte; Clays, Els; Tency, Inge; Leye, Els
Abstract Background health professionals in Belgium are confronted with female genital mutilation (FGM). To date, no survey to assess knowledge, attitudes and practices on FGM was conducted among midwives in the Northern region of Belgium. Objective the objective of this study was to assess the knowledge, attitude and practices of Flemish midwives regarding female genital mutilation (FGM). Design we used a quantitative design, using KAP study (semi-structured questionnaire). Setting labour wards, maternity wards and maternal intensive care units (MIC) in 56 hospitals in Flemish region of Belgium. Participants 820 midwives, actively working in labour wards, maternity wards and maternal intensive care units (MIC). Findings 820 valid questionnaires (40.9%) were returned. More than 15% of the respondents were recently confronted with FGM. They were mostly faced with the psychological and sexual complications caused by FGM. Few respondents were aware of existing guidelines regarding FGM in their hospitals (3.5%). The results also showed that only 20.2% was aware of the exact content of the law. The majority of midwives condemned the harmful traditional practice: FGM was experienced as a form of violence against women or a violation of human rights. Only 25.9% declared that FGM forms a part of their midwifery program. The vast majority of respondents (92.5%) indicated a need for more information on the subject. Key conclusions this study indicated that midwives in Flanders are confronted with FGM and its complications and highlighted the gaps in the knowledge of Flemish midwives regarding FGM. This may interfere with the provision of adequate care and prevention of FGM for the new-born daughter. Implications for practice there is an important need for appropriate training of (student)midwives concerning FGM as well as for the development and dissemination of clear guidelines in Flemish hospitals.